Can mental health legal representation and advocacy contribute to personal recovery?. (3rd July 2018) - Milbourn, Ben; Martin, Robyn; ,; Overheu, Hannah; Schalk, Danielle
ABSTRACT: Objective: Mental health legal advocacy services play a pivotal role in promoting the legal and social rights and increased participation in decision making for people diagnosed with a mental illness. Traditionally, recovery and mental health legal advocacy were not linked. The purpose of this study was to determine if elements of the CHIME (connectedness, hope, identity, meaning and empowerment) recovery framework can be reflected in activities such as legal representation and advocacy delivered by mental health law advocates. Method: Secondary analysis was undertaken on data collected in an evaluation of a mental health law centre. Analysis involved deductive coding and thematic analysis. Data were compared and contrasted to the five elements of the CHIME framework. Results: Four out of five CHIME elements were identified. These included connectedness with law centre staff, messages of hope from staff, experiences of empowerment and validation which informed a positive sense of identity. Discussion: The results invite mental health law centres to consider their role in influencing personal recovery journeys through their advocacy and legal representation activities.